Environmental obligations auditable of hydrocarbon commercialization establishments in San Martin, Peru - Bazan Suarez, Daimer Ely (2024)
Objective: The objective of the present investigation was to determine the non-compliance with the auditable environmental obligations of the hydrocarbon commercialization establishments of the Department of San Martin, from the perspective of the beginning of the Administrative Sanctioning Procedure (PAS), during the years 2019 and 2020. Methods: The methodology adopted involved the review and analysis of documentary information, the which consisted of the auditable environmental obligations recommended at the beginning of the PAS in the supervision reports developed by the supervisory authority of the Environmental Assessment and Oversight Agency (OEFA) and, likewise, by the results of the sub-directorial resolutions for the beginning of the PAS issued by the instructing authority of the OEFA. Results: The results, in base to the analyzed facts admitted to beginning of the PAS by the OEFA instructor authority, allude to the fact that non-compliance with the environmental obligations of the 49 establishments under study, located in the Department of San Martin, was of the13.54 % and 14.28 % between the years 2019 and 2020, respectively. Conclusions: Therefore, it is concluded that the hydrocarbon commercialization establishments of the Department of San Martin present non-compliance with their auditable environmental obligations that are detected in the supervisory actions of the supervisory authority and admitted by the instruction authority of the OEFA.